The effect of curcumin supplementation on delayed‐onset muscle soreness, inflammation, muscle strength, and joint flexibility: A systematic review and dose–response meta‐analysis of randomized controlled trials. (16th May 2022) - Beba, Mohammad; Mohammadi, Hamed; Clark, Cain C. T.; Djafarian, Kurosh
Abstract: To quantify the effects of curcumin supplementation on exercise‐induced muscle damage, muscle soreness, inflammatory biomarkers, muscle strength, and joint flexibility via assessment of creatine kinase (CK), visual analogue scale (VAS) score, maximal voluntary contraction (MVC), and range of motion (ROM), respectively. Online databases, including PubMed, Google Scholar, and Scopus, were searched up to February 2021. RevMan® software (version 5.3) was used for assessing the risk of bias to assess the quality of studies. The mean differences (MD) and confidence intervals (95% CI) of CK activity (IU/L), VAS score, tumor necrosis factor (TNF‐α) (pg/ml), interleukin‐6 (IL‐6) (pg/ml), IL‐8 (pg/ml), MVC (nm) and ROM (degree) were pooled using a random‐ or fixed‐effect model. Between‐study heterogeneity was assessed using χ‐square or I 2 statistic. Ten trials met the eligibility criteria and were included in the pooled analysis. Meta‐analysis showed that curcumin supplementation significantly reduced serum CK activity [WMD = −65.98 IU/L, 95% CI (−99.53 to −32.44)], muscle soreness [WMD = −0.56, 95% CI (−0.84 to −0.27)], and TNF‐α concentration [WMD = −0.22 pg/ml, 95% CI (−0.33 to −0.10)]. Also, curcumin supplementation elicited significant improvements in MVC [WMD = 3.10 nm, 95% CI (1.45–4.75)] and ROM [WMD = 6.49°, 95% CI (3.91–9.07)], although no significant changes in IL‐6 and IL‐8 levels were found. Dose–response analysis indicated that there is a significant non‐linear association between the daily dose and the final effect size regarding TNF‐α. Curcumin supplementation may improve some aspects of DOMS, including muscle damage, muscle soreness, inflammation, muscle strength, and joint flexibility. Further, well‐designed and high‐quality studies with larger sample sizes are needed to ascertain the long‐term effects and safety of curcumin supplementation.